Extended abstract ASID colloquium 2024 - UiTM, Pusat Asasi (Pusat Asasi, UiTM Cawangan Dengkil, 2024)
Centre of Foundation Studies, Universiti Teknologi MARA (UiTM) Cawangan Selangor Kampus Dengkil present the first extended abstracts of ASiD Colloquium Series 2024. These wide-ranging perspectives embody the spirit of collaboration necessary to address the complex challenges faced by education today. The research reflects expertise and significant steps taken in the effort of building a sustainable future in education.